Application of Biophilic Criteria in Libraries: Oodi Helsinki Central Library - Avinç, Güneş Mutlu; Taş, Aslı (Gazi Üniversitesi, 2024)
[Abstract Not Available]
Keywords: Mimari Tasarım; Mimarlık (Diğer)